Phantom limb pain relieved with different modalities of central nervous system stimulation: a clinical and functional imaging case report of two patients. - Nandi, D; Yianni, J; Humphreys, J; Wang, S; O'sullivan, V; Shepstone, B; Stein, J; Aziz, T (2004)
Phantom limb pain (PLP) is a type of neuropathic pain syndrome that has evoked much interest in scientific and clinical fields. The condition is often intractable and severely debilitating. Though there are anecdotal reports in the literature of successful management of individual cases with brain and spinal cord stimulation, it has not been possible to develop a system of management that is consistently successful, mainly due to the paucity of basic neurophysiological data about PLP and its pathways in the central nervous system (CNS). Functional imaging offers a way of collecting information about the basic mechanisms and pathways of PLP from patients without the excessive risk of more invasive penetrating electrode studies or the questionable reliability of animal data. There have been very few studies that have looked at the direct effect of CNS stimulation on regional brain activation and correlation with the pain state. We describe two cases of PLP that have been satisfactorily treated with CNS stimulation (motor cortex and then periventricular gray in one and spinal cord in the other) and have been subjected to single photon emission computed tomography (SPECT) studies when in pain and then during stimulation with recorded pain relief. We found that regardless of the site of stimulation in the CNS, pain relief is associated with blood flow changes in similar areas of the brain, mainly the parietal and cingulate cortex and also in the thalamic nuclei and the central gray matter. Further studies of this kind should reveal more about the complex mechanisms of PLP and other forms of neuropathic pain.